2018
DOI: 10.1007/s13202-018-0564-y
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of air–foam flooding in Wuliwan District 1 of Jing’an Oilfield

Abstract: Air-foam flooding is an important mean to reduce water cut, improve oil production rate, enhance oil displacement efficiency and oil recovery in old oilfield. Because of high cost of core displacement experiment, numerical simulation is an important method to get optimal injection-production parameters of air-foam flooding, which can improve displacement effect and direct field test in Wuliwan District 1 of Jing'an oilfield. Based on laboratory experiment of air-foam flooding, parameters including model compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Therefore, improving the swept volume and oil displacement efficiency of injected water is the major method to enhance the recovery of remaining oil . Based on the technological innovation and field application, it is confirmed that chemical flooding technology is able to substantially enhance oil recovery of the mature reservoir. , Related technologies include polymer flooding, surfactant flooding, alkali-free binary compound flooding, foam flooding, etc. Currently, nanoparticles have been used as additives in the polymer, surfactant, and foam for further improving oil recovery by changing the wettability, reducing the interfacial tension, and improving the mobility ratio. , These technologies have been applied in many oilfields and achieved significant economic benefits .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improving the swept volume and oil displacement efficiency of injected water is the major method to enhance the recovery of remaining oil . Based on the technological innovation and field application, it is confirmed that chemical flooding technology is able to substantially enhance oil recovery of the mature reservoir. , Related technologies include polymer flooding, surfactant flooding, alkali-free binary compound flooding, foam flooding, etc. Currently, nanoparticles have been used as additives in the polymer, surfactant, and foam for further improving oil recovery by changing the wettability, reducing the interfacial tension, and improving the mobility ratio. , These technologies have been applied in many oilfields and achieved significant economic benefits .…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen foam flooding is a technology that can effectively EOR by reducing the water-oil mobility ratio of heavy oil reservoirs and improving the viscous fingering of water flooding, and the nitrogen foam flooding has the two unique advantages of profile control and oil displacement. The development efficiency of heavy oil reservoirs and improving economic benefits has a guiding significance [22][23][24][25][26][27][28]. The application of nitrogen foam flooding techniques to unconventional reservoirs has recently been investigated by many researchers.…”
Section: Introductionmentioning
confidence: 99%